Outcome of reconstruction for duplication of the thumb in adults aged over 40. - Arumugam, Manohar; Beard, A. J. (World Scientific Publishing, 2011)
Congenital duplication of the thumb is usually reconstructed by 18 months of age. This paper reports satisfactory outcome following reconstruction of two Wassel Type IV duplicate thumbs in adults aged over 40. Both achieved a good outcome based on Tada's criteria and a subjective Visual analogue score 8.